2022
DOI: 10.3390/ijerph19137999
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neighborhood Physical and Social Environment on Physical Function among Japanese Community-Dwelling Older Adults: A One-Year Longitudinal Study

Abstract: Previous studies have shown a relationship between physical and social aspects of the neighborhood environment (e.g., built environment, safety) and physical function in older adults. However, these associations are unclear in older Asian adults because longitudinal studies are lacking. This study examined the effects of neighborhood physical and social environment on longitudinal changes in physical function among Japanese older adults. We analyzed 299 Japanese community-dwelling adults aged ≥65 years. Neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…We found that the knowledge of SARS-CoV-2 infection countermeasures increases mental stress and that the effect is particularly large in community-dwelling older people who feel lonely or who have a decline in cognitive function 21 ) . In addition, although it was not included in the survey items of this study, we considered that the relationship between fear of falling and fatigue 22 ) and the effects of neighborhood physical and social environment 23 ) cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the knowledge of SARS-CoV-2 infection countermeasures increases mental stress and that the effect is particularly large in community-dwelling older people who feel lonely or who have a decline in cognitive function 21 ) . In addition, although it was not included in the survey items of this study, we considered that the relationship between fear of falling and fatigue 22 ) and the effects of neighborhood physical and social environment 23 ) cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%